2012
DOI: 10.1007/s11033-012-2088-8
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of the fungal pathogen Metarhizium spp., causing epizootics in Chinese burrower bugs in the Jingting Mountains, eastern China

Abstract: Based on the internal transcribed spacer and inter-simple sequence repeats (ISSR), the phylogenetic relationship and genetic diversity of Metarhizium spp., pathogens found in Chinese burrower bugs, Schiodtella formosana, were analyzed. The results showed that the causative agents of the epizootic green muscardine disease in populations of S. formosana were actually composed of M. anisopliae and its sister species, M. robertsii. The genetic structure of Metarhizium spp. populations were assessed using ten ISSR.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 41 publications
0
4
0
2
Order By: Relevance
“…Molecular markers have been widely used for the identification, taxonomy, evolution, as well as genetic diversity of bacteria, protozoa, fungi, plants, and animals (17)(18)(19)(20)(21)(22)(23)(24), such as restriction fragment length polymorphism (RFLP) (25), random amplified polymorphic DNA (RAPD) (26), amplified fragment length polymorphism (AFLP) assays (27), simple sequence repeats (SSR) (28), inter-simple sequence repeats (ISSR) (29,30), and single-nucleotide polymorphisms (SNP) (31). Several reports on genetic diversity of V. virens have been published in recent years.…”
mentioning
confidence: 99%
“…Molecular markers have been widely used for the identification, taxonomy, evolution, as well as genetic diversity of bacteria, protozoa, fungi, plants, and animals (17)(18)(19)(20)(21)(22)(23)(24), such as restriction fragment length polymorphism (RFLP) (25), random amplified polymorphic DNA (RAPD) (26), amplified fragment length polymorphism (AFLP) assays (27), simple sequence repeats (SSR) (28), inter-simple sequence repeats (ISSR) (29,30), and single-nucleotide polymorphisms (SNP) (31). Several reports on genetic diversity of V. virens have been published in recent years.…”
mentioning
confidence: 99%
“…Metarhizium anisopliae and B. bassiana account for the vast majority [ 47 ]. M. rileyi is a dimorphic fungus with slow growth and development [ 48 ], and its advantages in soil environments or some insect hosts may not be obvious [ 49 ]. Notably, this study identified 31 strains of M. rileyi from different regions of Yunnan Province, China, and they were all derived from the same host, S. frugiperda .…”
Section: Discussionmentioning
confidence: 99%
“…(M. anisopliae and its sister species, M. robertsii), pathogens found in Chinese burrower bugs populations (Schiodtella formosana), were assessed using ISSR. They differentiated into two main clades including over 71% of all strains causing epizootics, with a similarity of 83% (LUAN et al, 2013).…”
Section: Molecular Characterizationmentioning
confidence: 99%